PENGARUH FAKTOR LINGKUNGAN DAN KEPUASAN PENGAJARAN KEWIRAUSAHAAN TERHADAP KETERAMPILAN BERWIRAUSAHA MAHASISWA - Ulviah Azizah; Keumala Hayati (Yayasan Nusantara Hasana Berdikari, 2026)
This Study Analyzes The Influence Of Environmental Factors And Entrepreneurship Teaching Satisfaction On The Entrepreneurial Skills Of University Students In Bandar Lampung. Data Were Collected Via Questionnaires From 250 Respondents Selected Through Purposive Sampling. Data Analysis Was Conducted Using Multiple Linear Regression With Spss Software. The Results Indicate That Environmental Factors And Entrepreneurship Teaching Satisfaction Have A Significant Effect. An R-Square Value Of 0.657 Shows That These Two Variables Contribute 65.7% To The Entrepreneurial Skills Variable, While The Remaining 34.3% Is Influenced By Other Factors. This Research Suggests That Universities Should Optimize Environmental Factors By Providing Supportive Entrepreneurship Facilities And Enhancing Teaching Quality Through A More Practice-Oriented Approach To Effectively Strengthen Students' Entrepreneurial Skills.